Relationship of insulin resistance with recurrent pregnancy loss - Wani, Asifa Ali; Gul, Irfan; Jabeen, Farhat; Kaul, Shiveta; Lone, Farhat Ali; Akhter, Gulshan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The recurrent pregnancy loss (RPL) is defined as two and more failed pregnancies as documented by ultrasound and histopathological examination and suggested some assessment after each loss with a thorough evaluation after three or more losses. RPL is one of the most frustrating and difficult areas in reproductive medicine because the aetiology is often unknown and there are few evidence based diagnostic and treatment strategies. Methods: 150 Non pregnant females were taken as both cases and controls in the study. All the pregnancy losses were documented by ultrasound or histological examination after uterine curettage. The control group consisted of women with no RPL with at least one live birth. These two groups were matched on the basis of age and BMI. All the women underwent following examinations, viz. Hysterosalpingography, karyotype of both partners, serum TSH, FT4, prolactin and antibodies for APLA. In addition blood sample were taken for fasting serum glucose and serum insulin level later insulin resistance was calculate using three parameters Fasting insulin > 20IU/ml. Diagnostic of Insulin Resistance. (2) Fasting glucose / Fasting insulin. A ratio of < 4.5 being diagnostic of insulin resistance. (3) HOMA IR. FG (mg/dl) x FPI (IU/ml) FG (mmol/l) x FPI (IU/ml) ------------------------------------ OR ----------------------------------- 405 22.5 Where 1 mmol/l = 18mg/dl, A value of > 4.5 being diagnostic of insulin resistance. Results: 150 patients were enrolled in this study among which 75 were selected as cases and 75 as controls after fulfilling inclusion and exclusion criteria with mean age cases group was28.4+2.37 years and 29.1+2.70 years in control group mean miscarriage rate in study group was 3.17+83 and control group with 0.35+0.48 with statistically significant difference. Mean fasting glucose (96.5+ 7.86) mg/dl, Fasting Insulin (14.1±5.91) IU/ml. Mean Glucose Insulin ratio (8.1±3.39), HOMA-IR (3.4 ±1.51) in the study group and in control group mean fasting glucose was (87.1+11.49) mg/dl, Fasting Insulin (6.9 ± 4.99) IU/ml. Mean Glucose Insulin ratio (17.8 ±11.44), HOMA-IR (1.5 ±1.27) respectively with statistically significant difference. Conclusions: In women with recurrent pregnancy loss fasting insulin and insulin resistance are higher than those in women without spontaneous abortion. The most sensitive parameter for calculating insulin resistance was found to be fasting insulin followed by HOMA – IR and followed by fasting glucose/fasting insulin ratio. It is therefore important to recommend a fasting insulin and fasting glucose level while evaluating a case of recurrent pregnancy loss to assess for insulin resistance.